Pengembangan Media Game Card Pada Pembelajaran Novel Di SMA Kelas XII - Linda Ocviliana; Munaris Munaris; Kahfie Nazaruddin (FKIP Universitas Lampung, 2019)
This research aims to develop a game card learning media with the aim of learning to analyze the content and linguistics of novels in Class XII Senior High School. The researcher choose to make a question and answer card game because it was possible to create learning media consisting of questions that were accompanied by images, so that the media developed could stimulate students ability to understand the lesson. Development of a game card is done by following the steps as follows, named (1) needs analysis; (2) planning; (3) draft development; (4) stage validation expert; and (5) revisions. The results of research and development are learning media in the form of feasibility learning media in accordance with the results of validation. After the the results of the validation of material experts and media experts, the revision stage was carried out to create tools that were declared appropriate for use in the learning process.Penelitian ini bertujuan untuk mengembangkan sebuah media pembelajaran game card dengan tujuan pembelajaran menganalisis isi dan kebahasaan novel di SMA Kelas XII. Peneliti memilih membuat game card tanya jawab karena memungkinkan untuk membuat media pembelajaran yang terdiri dari soal pertanyaaan yang disertai gambar sehingga media yang dikembangkan mampu merangsang kemampuan siswa dalam memahami materi. Pengembangan game card dilakukan dengan mengikuti langkah-langkah sebagai berikut, yaitu (1) analisis; kebutuhan; (2) perencanaan; (3) pengembangan draft; (4) tahap validasi ahli; dan (5) revisi. Hasil penelitian dan pengembangan adalah media pembelajaran dalam bentuk game card tanya jawab sesuai dengan hasil validasi yang dinyatakan layak. Kemudian dari hasil validasi ahli materi dan ahli media dilakukan tahap revisi untuk menciptakan alat bantu yang dinyatakan telah layak untuk digunakan dalam proses pembelajaran.Kata kunci : media pembelajaran, game card, dan novel